2016
DOI: 10.1080/15476286.2016.1203501
|View full text |Cite
|
Sign up to set email alerts
|

ADAR1 deletion induces NFκB and interferon signaling dependent liver inflammation and fibrosis

Abstract: Adenosine deaminase acting on RNA (ADAR) 1 binds and edits double-stranded (ds) RNA secondary structures found mainly within untranslated regions of many transcripts. In the current research, our aim was to study the role of ADAR1 in liver homeostasis. As previous studies show a conserved immunoregulatory function for ADAR1 in mammalians, we focused on its role in preventing chronic hepatic inflammation and the associated activation of hepatic stellate cells to produce extracellular matrix and promote fibrosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 37 publications
6
29
0
Order By: Relevance
“…In our earlier report, we demonstrated that IL-6 mediates the direct activation of HSCs in hepatocyte-specific ADAR1 knock-out mice [15]. The current study further characterized this role and demonstrated that both the MAPK and JAK/STAT3 signal transduction pathways are required for IL-6 activity.…”
Section: Discussionsupporting
confidence: 71%
“…In our earlier report, we demonstrated that IL-6 mediates the direct activation of HSCs in hepatocyte-specific ADAR1 knock-out mice [15]. The current study further characterized this role and demonstrated that both the MAPK and JAK/STAT3 signal transduction pathways are required for IL-6 activity.…”
Section: Discussionsupporting
confidence: 71%
“…In addition, CAR is involved in the exacerbation of hepatic fibrosis in a mouse dietary model of nonalcoholic steatohepatitis (Yamazaki et al, 2007). A recent study reported that hepatocyte-specific ADAR1 knockout mice display massive liver damage with fibrogenesis, suggesting that ADAR1 restrains the development of hepatic fibrosis (Ben-Shoshan et al, 2017). Combined with the present findings that ADAR1 negatively regulates CAR expression, a possibility is surmised that ADAR1 has a role in protecting the liver from fibrosis by repressing CAR expression.…”
Section: Discussionsupporting
confidence: 74%
“…Nevertheless, we reveal for the first time that the presence of unedited endogenous dsRNAs triggered the aberrant activation of MDA5 in ADAR1‐deficient T cells, which was deleterious for their maturation. This is unique because ADAR1‐deficient cells usually exhibit widespread apoptosis with the enhanced expression of type I ISGs, which results in a severe reduction in the number of corresponding cells, such as hematopoietic stem cells, erythroid cells, B cell lineage cells, and hepatocytes . It is well known that treatment with poly(I:C), which mimics viral dsRNA and is commonly used as an MDA5 ligand, triggers pro‐apoptotic signaling in various cells .…”
Section: Discussionmentioning
confidence: 99%